2014
DOI: 10.1155/2014/853826
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intravenous Lidocaine on Trigeminal Neuralgia: A Randomized Double Blind Placebo Controlled Trial

Abstract: Trigeminal neuralgia is the most common neuralgia. Its therapeutic approach is challenging as the first line treatment often does not help, or even causes intolerable side effects. The aim of our randomized double blind, placebo controlled, crossover study was to investigate in a prospective way the effect of lidocaine in patients with trigeminal neuralgia. Twenty patients met our inclusion criteria and completed the study. Each patient underwent four weekly sessions, two of which were with lidocaine (5 mgs/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 21 publications
2
52
0
Order By: Relevance
“…One RCT on the use of intravenous lidocaine in acute exacerbation was found . In this trial, a single dose of intravenous lidocaine (5 mg/kg over 60 min) was superior in reducing pain intensity compared to placebo during the first 24 h after the infusion.…”
Section: Section 2: Pharmacological Treatmentmentioning
confidence: 96%
“…One RCT on the use of intravenous lidocaine in acute exacerbation was found . In this trial, a single dose of intravenous lidocaine (5 mg/kg over 60 min) was superior in reducing pain intensity compared to placebo during the first 24 h after the infusion.…”
Section: Section 2: Pharmacological Treatmentmentioning
confidence: 96%
“…The latter can be purely neuropathic secondary to cranial neuropathies (ie, trigeminal neuralgia)34 or predominantly nociceptive secondary to temporomandibular disorders 35…”
Section: Phenomenology and Diagnostic Challengesmentioning
confidence: 99%
“…There are some clinical reports that patients with trigeminal neuralgia, local and intravenous administration of lidocaine effectively attenuates of intensity of pain, including allodynia and hyperalgesia (Kanai et al, 2006;Han et al, 2008;Stavropoulou et al, 2014). Present study indicated that local injection of resveratrol may act in a manner similar to injection of a local anesthetic agent.…”
Section: Functional Significance Of Suppression Of Nociceptive Stimulmentioning
confidence: 55%